Approaches in handling ethical challenges of cancer treatments and research in Nigeria (2009)
The diagnosis of cancer can devastate the physical, emotional, and socio-economic life of an individual. Caring for most cancer patients presents serious ethical challenges to physicians and other health workers. Inclusion of cancer patients in research could be no less challenging, These ethical problems become significantly magnified in the context of patients who have cancer in a low resource environment characterized by high illiteracy rate, poverty and poor health care infrastructure, Some of the ethical problems include: palliative care and end of life issues, particularly since most patients present in advanced stages, withholding or withdrawal Of life support, global equity and justice in drug availability, drug pricing, cancer research and breaking bad news, Adherence to ethical guidelines ill conducting cancer research would go a long way in reducing harms and unethical conducts. Similarly, the relevance of clinical and research ethics committees in resolving complex ethical issues in clinical practice has been suggested. However, where these are in place, the need for recourse to philosoph ical approach, especially virtue ethics in analyzing and resolving ethical concerns in clinical practice cannot be overemphasized. This paper highlights the burden of cancer in Nigeria and the ethical challenges of clinical management of cancer patients, using a case study. The role of clinical ethics and health research ethics committees as well as the justification for virtue ethics above principlism in handling ethical issues in cancer management and research in Nigeria were highlighted.